Riots in Lyon and Oldham: A comparative study - Prahl, Sabine (2011)
In recent years both Britain and France have witnessed riots by ethnic minority youth. This thesis will conduct a comparative study into the riots which broke out in Oldham in 2001 and Lyon in 2005. This is guided by two questions: firstly, why did riots erupt in these two cities; and secondly, why was it that Lyon‟s riots were composed of two parties (police and ethnic youth) and Oldham‟s riots three parties (police, ethnic youth and right wing activists)? This thesis will argue that the role of the police is central to answering both questions. Firstly, it will argue that harassment by the police created grievances that led to rioting. Secondly, it will argue that the different composition of the riots was caused by the nature of the harassment employed by the police, which was in turn influenced by the nature of the relationship between the state and the police